Factors Influencing Consumer Decisions to Purchase Hijab Products Online on Instagram Social Media - Latief, Fitriani; Murti, Rahel Sri (Advances in Business & Industrial Marketing Research, 2023)
Purpose: This study investigates the influence of cultural, social, individual, and psychological factors on consumer purchasing decisions within the digital marketplace. The hypothesis is that individual and psychological factors influence purchasing behavior more significantly than cultural and social factors. Research Design and Methodology: The study employs a quantitative research design using a structured questionnaire validated for reliability. The survey was administered to a diverse demographic sample of young adults who are active users of online shopping platforms. Data were collected and analyzed using regression analysis to determine the significance of each factor on purchasing decisions. Findings and Discussion: The results indicate that individual and psychological factors significantly affect consumer purchasing decisions, whereas cultural and social factors have no significant impact. This suggests that personal preferences and psychological motivations are more influential than traditional cultural or social considerations in shaping consumer behavior in digital markets. Implications: The findings imply that businesses should prioritize marketing strategies that focus on individual and psychological factors to enhance consumer engagement and drive sales. Further research is recommended to examine these factors across different cultural contexts to broaden our understanding of consumer behavior in a global digital environment.